The relation between barrier-free environment perception and campus commuting satisfaction - Li, Jiang; Zhang, Chuyu; Cai, Xiaoxi; Peng, You; Liu, Shaobo; Lai, Wenbo; Chang, Yating; Liu, Yudan; Yu, Liang (Frontiers in Public Health, 2023)
The COVID-19 pandemic, which started in the last quarter of 2019, has had a significant impact on urban transportation. With increasing demand for urban transport, the internal roads and public spaces of university campuses will play an important role in facilitating commuting and communication between various functional zones. While considerable research has been conducted on route planning, pedestrian-vehicle segregation, and safety management in the internal transportation environment of university campuses, empirical investigations exploring barrier-free inclusive campus environment design and the subjective evaluation of road and public space users in the aftermath of the COVID-19 pandemic are lacking. Recent developments in travel behaviour models and positive psychology have led to an increased focus on the correlation among subjective 2 perceptions, attitudes, emotions, and commuting satisfaction in urban transportation and planning design. To elucidate this relationship, a study was conducted on the new campus of Central South University in Changsha, Hunan Province, China. A structural equation model was constructed from 312 valid samples to analyse the relationship between commuting satisfaction and the barrier-free environment perception of university students regarding the internal transportation environment of the campus. The results revealed that individuals' instantaneous barrier-free environment perceptions and long-term established positive emotions had a significant positive effect on commuting satisfaction. Furthermore, positive emotions were found to mediate the relationship between commuting attitudes induced by COVID-19, barrier-free environment perceptions, and commuting satisfaction. The results of this study provide a theoretical basis for the necessity of accessibility design in the post-COVID era and present ideas for the planning and construction of barrier-free campus environments based on convenient and inclusive design from the perspective of understanding users.